Optimization of the Injection Mold Runner System of the Transport Means Plastic Parts - Cechmanek, Damian; Kohar, Robert; Brumercik, Frantisek; Lukac, Michal; Fiacan, Jakub (Communications - Scientific Letters of the University of Zilina, 2023)
This paper describes the optimization of dimensions of the individual injection mold runner system of the plastic part used as the frame for various devices in transport means. Nowadays, the great emphasis is placed on the production time and finances associated with design and production. As a result, simulations are being employed increasingly. This paper aims to describe the design the optimum size and shape of the sprues and runners required for proper filling and to simulate the injection molding process to avoid problems and defects that tend to be caused by an incorrectly sized runner system. As a result, some adjustments were made to the size of the runner system to eliminate problems with underfilling, overfilling, air traps and weld lines. The difficulties with the original design were fixed by the optimized solution, which improved the monitored parameters. Additionally, the technological parameters of the injection process were modified, resulting in lower stress on the injection mold in the injection process.
Keywords: runner system; injection molding; injection mold; constructional design; analysis